2015
DOI: 10.1016/j.neuron.2015.08.037
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine Prediction Errors in Reward Learning and Addiction: From Theory to Neural Circuitry

Abstract: Summary Midbrain dopamine (DA) neurons are proposed to signal reward prediction error (RPE), a fundamental parameter in associative learning models. This RPE hypothesis provides a compelling theoretical framework for understanding DA function in reward learning and addiction. New studies support a causal role for DA-mediated RPE activity in promoting learning about natural reward; however, this question has not been explicitly tested in the context of drug addiction. In this review, we integrate theoretical mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
273
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 322 publications
(284 citation statements)
references
References 191 publications
(290 reference statements)
10
273
1
Order By: Relevance
“…For example, opioid agonists and drugs that enhance endocannabinoid signaling by interfering with endocannabinoid deactivation increase social play (Trezza et al, 2010). There are several reasons to hypothesize that dopaminergic neurotransmission also has a modulatory role in social play: (1) dopamine plays an important role in certain components of reward processes, such as incentive motivation, incentive salience, and reward prediction (Kelley, 2004;Barbano and Cador, 2007;Berridge, 2007;Salamone and Correa, 2012;Keiflin and Janak, 2015); (2) dopamine utilization increases during social play (Panksepp, 1993); (3) systemic administration of dopamine receptor antagonists reduces social play (Beatty et al, 1984;Niesink and Van Ree, 1989;Siviy et al, 1996;); (4) neonatal 6-hydroxydopamine lesions, which induce profound depletion of striatal dopamine, alter the structure of social play behavior (Pellis et al, 1993); and (5) enhancing dopaminergic activity by blockade of the dopamine transporter increases the motivation for social play (Achterberg et al, 2016). However, contrary to the expectation that drugs that increase dopaminergic neurotransmission would then enhance social play, inconsistent effects have been reported after systemic treatment with dopamine receptor agonists or dopamine reuptake inhibitors (Achterberg et al, 2014;Beatty et al, 1984;Niesink and Van Ree, 1989;Siviy, 1998;Siviy et al, 1996;Vanderschuren et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…For example, opioid agonists and drugs that enhance endocannabinoid signaling by interfering with endocannabinoid deactivation increase social play (Trezza et al, 2010). There are several reasons to hypothesize that dopaminergic neurotransmission also has a modulatory role in social play: (1) dopamine plays an important role in certain components of reward processes, such as incentive motivation, incentive salience, and reward prediction (Kelley, 2004;Barbano and Cador, 2007;Berridge, 2007;Salamone and Correa, 2012;Keiflin and Janak, 2015); (2) dopamine utilization increases during social play (Panksepp, 1993); (3) systemic administration of dopamine receptor antagonists reduces social play (Beatty et al, 1984;Niesink and Van Ree, 1989;Siviy et al, 1996;); (4) neonatal 6-hydroxydopamine lesions, which induce profound depletion of striatal dopamine, alter the structure of social play behavior (Pellis et al, 1993); and (5) enhancing dopaminergic activity by blockade of the dopamine transporter increases the motivation for social play (Achterberg et al, 2016). However, contrary to the expectation that drugs that increase dopaminergic neurotransmission would then enhance social play, inconsistent effects have been reported after systemic treatment with dopamine receptor agonists or dopamine reuptake inhibitors (Achterberg et al, 2014;Beatty et al, 1984;Niesink and Van Ree, 1989;Siviy, 1998;Siviy et al, 1996;Vanderschuren et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, when a reward does not fulfill expectations, DA neuronal activity decreases. This pattern of DA cell activity is the basis of reward prediction error (RPE) theory [17][18][19][20] , which describes an essential mechanism through which organisms learn to flexibly alter their behavior when the costs and benefits associated with different courses of action shift. Although the relevance of RPEs in value-based learning is widely acknowledged, little is known about how different VTA target regions process these DA-mediated error signals, and how this ultimately leads to adaptations in behavior.…”
mentioning
confidence: 99%
“…Luo et al [58], Li et al [59], and Hayashi et al [60] found that serotonin neurons in the dorsal raphe nucleus can encode reward signals. Some physiological and theoretical works [17,18,[61][62][63] focus on D1 and D2 receptors in the ventral striatum and suggested that they play an important role in computing reward-prediction error. Future neural circuit modeling effort would need to incorporate such findings.…”
Section: Complexitymentioning
confidence: 99%